Police Matters The Everyday State and Caste Politics in South India, 1900-1975 - Kumar, Radha (Cornell University Press, 2021)
"Police Matters moves beyond the city to examine the intertwined nature of police and caste in the Tamil countryside. Radha Kumar argues that the colonial police acted as tools of the state in deploying rigid notions of caste, refashioning rural identities in a process that has cast long postcolonial shadows. Kumar draws on unexplored police archives to enter the dusty streets and market squares where local constables walked, following their gaze and observing their actions towards potential subversives. Station records present a textured view of ordinary interactions between police and society, showing that state coercion was not only exceptional and spectacular; it was also subtle and continuous, woven into everyday life. The colonial police categorized Indian subjects based on caste to ensure the security of agriculture and trade, and thus the smooth running of the economy. Among policemen and among the objects of their coercive gaze, caste became a particularly salient form of identity in the politics of public spaces. Police Matters demonstrates that, without doubt, modern caste politics have both been shaped by, and shaped, state policing. Thanks to generous funding from the Andrew W. Mellon Foundation, through The Sustainable History Monograph Pilot, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellopen.org) and other repositories."